2018
DOI: 10.1038/s41598-018-35789-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis and Biomarker Study for Alzheimer’s Disease

Abstract: Revealing the relationship between dysfunctional genes in blood and brain tissues from patients with Alzheimer’s Disease (AD) will help us to understand the pathology of this disease. In this study, we conducted the first such large systematic analysis to identify differentially expressed genes (DEGs) in blood samples from 245 AD cases, 143 mild cognitive impairment (MCI) cases, and 182 healthy control subjects, and then compare these with DEGs in brain samples. We evaluated our findings using two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 50 publications
4
63
2
Order By: Relevance
“…Considering both internal and external validations, this study showed that all DEGs and the DEGs with CFG could accurately identify AD. Among the previous studies listed in Table 1, a study by Li et al 20 classified AD patients most accurately in the ANM dataset. However, in their study 20 , it seems that both ANM1 and ANM2 datasets were used for selecting features (six genes).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering both internal and external validations, this study showed that all DEGs and the DEGs with CFG could accurately identify AD. Among the previous studies listed in Table 1, a study by Li et al 20 classified AD patients most accurately in the ANM dataset. However, in their study 20 , it seems that both ANM1 and ANM2 datasets were used for selecting features (six genes).…”
Section: Discussionmentioning
confidence: 99%
“…Among the previous studies listed in Table 1, a study by Li et al 20 classified AD patients most accurately in the ANM dataset. However, in their study 20 , it seems that both ANM1 and ANM2 datasets were used for selecting features (six genes). After curating the six AD-related genes, they used them as input features for the SVM model, yielding AUCs of 0.86 and 0.873 when testing ANM1 and ANM2, respectively 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the majority of DEGs were down-regulated (270), a significant number (84) were upregulated (Supplementary Tables S4, S5). Among these several belong to the ribosome pathway, which is interesting since alterations of these genes might be involved in Alzheimer's disease (Li et al, 2018). CSEA also indicated that some of the DEGs were enriched in specific brain regions and/or cell types.…”
Section: Discussionmentioning
confidence: 99%